Mitigation of ionospheric effects on GNSS positioning at low latitudes - Park, J.; Vadakke Veettil, Sreeja; Aquino, Marcio; Yang, Lei; Cesaroni, Claudio (Wiley, 2017)
Ionospheric conditions at low latitudes are extremely harsh due to the frequent occurrence of scintillation and the presence of strong TEC gradients. For this study, the São Paulo state region in Brazil is chosen as a test area. This study presents a strategy to mitigate the ionospheric impact on RTK positioning with an experimental result. The proposed strategy explores two approaches that can be applied simultaneously: a) to mitigate the scintillation effect on the GNSS signals by refining the stochastic model of the corresponding observations and b) to precisely estimate the residual double difference ionospheric delay by exploiting an accurate TEC map. The strategy was tested on a long baseline kinematic processing under strong scintillation conditions (DOY21 in 2014). Significant improvements were observed when the combined use of the two mitigation approaches described above was compared with the use of conventional state-of-the-art approaches.